Direct Measurement of Axial Momentum Imparted by an Electrothermal Radiofrequency Plasma Micro-Thruster - Charles, Christine; Boswell, Roderick W.; Bish, Andrew; Khayms, Vadim; Scholz, Edwin F. (Frontiers in Physics, 2016)
Gas flow heating using radio frequency plasmas offers the possibility of depositing power in the center of the flow rather than on the outside, as is the case with electro-thermal systems where thermal wall losses lower efficiency. Improved systems for space propulsion are one possible application and we have tested a prototype micro-thruster on a thrust balance in vacuum. For these initial tests, a fixed component radio frequency matching network weighing 90 g was closely attached to the thruster in vacuum with the frequency agile radio frequency generator power being delivered via a 50 ohm cable. Without accounting for system losses (estimated at around 50%), for a few 10 s of Watts from the radio frequency generator the specific impulse was tripled to 48 s and the thrust tripled from 0.8 to 2.4 milli-Newtons.